2015
DOI: 10.5966/sctm.2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Intracarotid Infusion of Mesenchymal Stem Cells in an Animal Model of Parkinson's Disease, Focusing on Cell Distribution and Neuroprotective and Behavioral Effects

Abstract: This study demonstrates that mesenchymal stem cells infused through the carotid artery do not efficiently cross the blood-brain barrier in rats with a Parkinson's disease-like degeneration of nigrostriatal neurons, unless a permeabilizing agent (e.g., mannitol) is used. The infusion did not reduce the neuronal damage and associated motor impairment, but abolished the motor abnormalities these animals typically show when challenged with a dopaminergic agonist. Therefore, although arterially infused mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 94 publications
1
35
0
Order By: Relevance
“…These authors correlated animal improvements with the increase in the local expression of BDNF and GDNF by transplanted MSCs. Recently, Cerri et al , also supporting the secretome theory, demonstrated that after transplantation of MSCs, functional balance of the dopaminergic system was restored; they attributed these outcomes to an in situ secretion of BDNF by MSCs.…”
Section: Discussionmentioning
confidence: 94%
“…These authors correlated animal improvements with the increase in the local expression of BDNF and GDNF by transplanted MSCs. Recently, Cerri et al , also supporting the secretome theory, demonstrated that after transplantation of MSCs, functional balance of the dopaminergic system was restored; they attributed these outcomes to an in situ secretion of BDNF by MSCs.…”
Section: Discussionmentioning
confidence: 94%
“…As for the application route of stem cells in patients suffering from neurodegenerative disorders, in our opinion, bm-SC might be best implanted intrathecally. Intravenous application ends up with most bm-SCs stuck in lung and liver (Fischer et al 2009), and the number of engrafted bm-SCs in the central nervous system will be minimal due to the lack of ability to easily cross the blood-brain barrier by these cells (Cerri et al 2015). On top of this, repeated intrathecal bm-SC transplantations proved to be safe and feasible, and are found most promising for the treatment of patients with neurological diseases (Pan et al 2019).…”
Section: Gsk-3βmentioning
confidence: 99%
“…The optimal route of MSC delivery and dosage regime are still debated (Kean et al, 2013 ; Richardson et al, 2013 ; Chang et al, 2014 ; Yavagal et al, 2014 ). The success of a systemic delivery depends very much on the ability of MSC to home to the site of injury and to access target tissues in case of a damaged or still regenerating vascularization (Cerri et al, 2015 ). Efficacious outcomes after intravenous delivery have repeatedly been reported (Semedo et al, 2009 ; Cruz et al, 2015 ; Rapp et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%